A goal-framing perspective on the important aspects of energy-efficient multifamily buildings - Mattsson, Pimkamol; Johansson, Maria (Frontiers in Psychology, 2022)
The growth of Sweden’s urban population necessitates new approaches for increasing the sustainability and energy efficiency of multifamily buildings. The development of such approaches will require a holistic and integrated understanding of the factors driving the decision making of both professionals who design buildings and end-users who live in them. This paper therefore uses the goal-framing theory to determine which aspects of multifamily buildings are considered important by these two groups of actors. An empirical study based on semi-structured interviews with professionals involved in building design and development (project developers, housing company representatives, architects, and engineers; N=15) was conducted to identify goals affecting the choices made during building design and development. In parallel, a questionnaire survey of building end-users (N=61) was conducted to determine which factors guided their choice of dwelling. It was found that professionals’ design choices were primarily governed by normative goals relating to environmental benefits but were also influenced by the other goals. These included gain goals relating to budgetary constraints and keeping the building’s operational and maintenance costs low. Hedonic goals were also important; some design choices were made with the aim of providing pleasant, comfortable, and convenient living environments, or of giving the buildings a distinct aesthetic or some other special feature. By comparing the professionals’ responses to the end-user surveys, it was found that the two groups had similar views concerning gain goals; both considered it important for apartments to be affordable and easy to maintain. However, their views on hedonic and normative goals differed markedly. The professionals sought to strike an optimal balance between different related aspects, whereas end-users placed greater importance on aspects relating to hedonic and gain goals when choosing dwellings. These findings provide a basis for constructive discussions on building design and development and the scope for creating buildings that encourage end-users to adopt sustainable living practices while also satisfying their needs and preferences.